2017
DOI: 10.1002/smll.201701644
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of Plasmonic Resonant Energy Transfer over Direct Electron Transfer in Substantially Enhanced Water Oxidation Activity of BiVO4 by Shape‐Controlled Au Nanoparticles

Abstract: The performance of plasmonic Au nanostructure/metal oxide heterointerface shows great promise in enhancing photoactivity, due to its ability to confine light to the small volume inside the semiconductor and modify the interfacial electronic band structure. While the shape control of Au nanoparticles (NPs) is crucial for moderate bandgap semiconductors, because plasmonic resonance by interband excitations overlaps above the absorption edge of semiconductors, its critical role in water splitting is still not ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 58 publications
(117 reference statements)
0
38
0
Order By: Relevance
“…BiVO 4 (BVO) is a model photoanode material with several desirable characteristics, such as a moderate band gap of 2.4–2.6 eV with a conduction band edge that is close to hydrogen evolution potential, relatively long minority carrier diffusion length, and reasonable surface activity and stability . However, due to the notoriously low electron mobility of BiVO 4 , a back‐illuminated configuration is typically used, which generates photocarriers near the back contact.…”
Section: Introductionmentioning
confidence: 99%
“…BiVO 4 (BVO) is a model photoanode material with several desirable characteristics, such as a moderate band gap of 2.4–2.6 eV with a conduction band edge that is close to hydrogen evolution potential, relatively long minority carrier diffusion length, and reasonable surface activity and stability . However, due to the notoriously low electron mobility of BiVO 4 , a back‐illuminated configuration is typically used, which generates photocarriers near the back contact.…”
Section: Introductionmentioning
confidence: 99%
“…I-t curves were recorded at 0.35 V (vs Ag/AgCl) with light on and off in the presence of 30 mM glucose. EIS was recorded within the frequency range of 0.1-10 6 Hz with signal amplitude of 5 mV in 100 mM PBS buffer (pH 7.4) containing 30 mM Glucose. Laser light sources of 450, 532, 652, 808 nm were used .…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…The interaction of incident light with the metallic surface can excite resonant collective oscillations of conduction electrons of noble metal nanoparticles. [6][7][8][9] Therefore the plasmonic nanostructures have been widely used in photocatalysts, photodetectors, bioanalysis, enzyme-like, and construction of photovoltaic devices. It has been reported that the polarization of the electronic system leads to locally strongly enhanced electromagnetic fields and increased absorption cross section of plasmonic nanostructures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of such efforts, a few candidates have been introduced and investigated extensively. The promising candidates are BiVO 4 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], Fe 2 O 3 [25][26][27][28][29][30][31][32], and BiFeO 3 [33][34][35]. Figure 2 shows the band gap energies and band edge positions of various semiconductors with respect to the water redox potential.…”
Section: Absorption Of Solar Radiationmentioning
confidence: 99%